2015
DOI: 10.1021/acs.jafc.5b00660
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis Process in Fermented Sausage Model Systems As Studied by NMR Relaxometry

Abstract: Proton NMR relaxation analyses were performed in sausage model systems (SMS) at different manufacturing times (0, 1, 3, 5, 7, and 9 days) to evaluate changes in water distribution and mobility. Three different water populations were identified, T2b (5-10 ms), T21 (30-70 ms), and T22 (100-300 ms), and the progress of ripening could be followed as a shift toward shorter relaxation times. In addition, the combined effect of adding commercial proteases (Pronase E and aspartyl proteinase) on protein breakdown and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…It was obvious that the overall trend of T 2 (T 2b , T 21 , T 22 ) significantly decreased (or left shift) ( Fig. 5 a & Table S3 ), which indicated that the protons derived from water or lipid in cooked SEYs bound more close with the matrix (proteins and lipids) in it [59] . The mobility of water (lipids) decreased might be explained by the gelation of SEYs, water fixed in gel network, promoted by heat (or ultrasonic) treatment, such as the gradual reduction of T 2b (A 2b ) ( Fig.…”
Section: Resultsmentioning
confidence: 98%
“…It was obvious that the overall trend of T 2 (T 2b , T 21 , T 22 ) significantly decreased (or left shift) ( Fig. 5 a & Table S3 ), which indicated that the protons derived from water or lipid in cooked SEYs bound more close with the matrix (proteins and lipids) in it [59] . The mobility of water (lipids) decreased might be explained by the gelation of SEYs, water fixed in gel network, promoted by heat (or ultrasonic) treatment, such as the gradual reduction of T 2b (A 2b ) ( Fig.…”
Section: Resultsmentioning
confidence: 98%
“…The first water component (T 2 b 1 ) detected was associated with the lack of a strong and well-organized composite system gel structure, as suggested by García García et al [22]. Other authors [23] have indicated that the shortest T2 relaxation time could be associated with water within the cell wall of the samples.…”
Section: Water Statementioning
confidence: 63%
“…Low filed NMR T2 relaxation time measurements demonstrated that the addition of these ingredients could induce the transference of water molecules from a loosely bound to tightly bound water fraction. Consequently, the presence of longer T 22 and shorter relaxation times (T 2b1 , T 2b2, T 21 ) suggests that the binding properties are stronger between water molecules and muscle tissue. The cooked sausage samples, with or without RF, GRF, or TS, showed similar trends in T2 relaxation times (Figures 1 and 2A).…”
Section: Water Statementioning
confidence: 99%
See 1 more Smart Citation
“…The following recent examples highlight the diversity of the processes that can be studied in this field. Garcìa et al studied the ripening step of fermented sausages. Several fermented sausages were prepared and analyzed after different ripening times.…”
Section: Applications Of Benchtop Nmr To the Study Of Bioprocessesmentioning
confidence: 99%